Disruption of the preB Cell Receptor Complex Leads to Decreased Bone Mass - Khass, Mohamed; Rashid, Harunur; Burrows, Peter D.; Bridges, S. Louis; Javed, Amjad; Schroeder, Harry W. (Frontiers in Immunology, 2019)
In the bone marrow, preB cells are found adjacent to the bone endosteum where bone synthesizing osteoblast and bone resorbing osteoclasts reside. Although there is evidence of interactions between preB and bone cells, the factors that contribute to such interactions are poorly understood. A critical checkpoint for preB cell development assesses the integrity of the nascent immunoglobulin μ heavy chain (HC) by testing whether it can participate in the formation of a preB cell receptor (preBCR), composed of the μ HC and surrogate light chain (LC). In this work we tested whether loss of preBCR components can affect bone synthesis. A panel of mice with sequential gene targeted blocks in preBCR formation or function [surrogate light chain component lambda 5 deleted (λ5-/-), transmembrane domain of µHC deleted (IgM-mem-/-) and CD19 preBCR coreceptor deleted (CD19-/-)] were evaluated for effects on postnatal bone synthesis. Postnatal bone mass was analyzed in six month old mice using μ-CT, histomorphometry and double calcein labeling. Both cortical and trabecular bone mass were significantly decreased in the femurs of the λ5 and IgM-mem deficient mice. Histomorphometric analysis showed a decrease in the numbers of osteoblasts and osteoclasts in all three mutant strains. Double calcein labeling revealed a significant decrease in dynamic synthesis and mineralization of bone in λ5-/- mice. Our data strongly suggest that interference with preBCR formation or function affects bone homeostasis independent of the presence or absence of mature B cells, and that components of the preBCR play important, and potentially distinct, roles in regulating adult bone mass.